KARAKTERISASI SIFAT MEKANIS KALENG MINUMAN (LARUTAN LASEGAR, POCARI SWEAT DAN COCA COLA) - Sri Mulyadi Dt. Basa; Fenima Halawa (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Detailed studies about characteristics of mechanical properties soft drinks cans (Lasegar Liquid, Pocari Sweat and Coca Cola) have been conducted. The characterisation on this experiment were investigated using hardness and tensile strength tests. It were observed that tensile strength is inversely proportional to concentration of aluminium on sample of soft drinks canes. Tensile strength decreased with increasing of aluminium concentration in sample. On the other hand, the hardness test show that the value of hardness are comparable to aluminium concentrations in sample. The hardness of soft drink cans increased with increasing of aluminium concentration in sample.Keywords : Tensile strength, hardness, soft drinks cans, aluminium.